Measure instrumental in Russian - Demjjanow, Assinja; Strigin, Anatoli (ZAS Papers in Linguistics, 2001)
We will argue that some seemingly adverbial free DPs in the instrumental in Russian which are traditionally termed measure instrumental are best understood as secondary predicates. We present the relevant syntactic assumptions and propose a semantics of this use of DPs in the instrumental. This proposal hears on the distinction between adjunct modification and secondary predication.